2003
DOI: 10.1038/sj.hdy.6800285
|View full text |Cite
|
Sign up to set email alerts
|

Analogous pleiotropic effects of insecticide resistance genotypes in peach–potato aphids and houseflies

Abstract: We show that single-point mutations conferring target-site resistance (kdr) to pyrethroids and DDT in aphids and houseflies, and gene amplification conferring metabolic resistance (carboxylesterase) to organophosphates and carbamates in aphids, can have deleterious pleiotropic effects on fitness. Behavioural studies on peach-potato aphids showed that a reduced response to alarm pheromone was associated with both gene amplification and the kdr target-site mutation. In this species, gene amplification was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 68 publications
(66 reference statements)
4
83
0
2
Order By: Relevance
“…Moreover, these mutations also appear to affect nerve functioning and behavior in insect species. For example, a pyrethroid‐resistant strain of Musca domestica responds differently to changes in temperature (Foster et al., 2003) and pyrethroid resistance in A. gambiae and A. aegypti is associated with a lowered ability of host seeking and an increased locomotor activity, respectively (Brito et al., 2013; Diop et al., 2015). It is therefore possible that we have missed a potential pleiotropic effect of the L1024V mutation on the behavior of T. urticae .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these mutations also appear to affect nerve functioning and behavior in insect species. For example, a pyrethroid‐resistant strain of Musca domestica responds differently to changes in temperature (Foster et al., 2003) and pyrethroid resistance in A. gambiae and A. aegypti is associated with a lowered ability of host seeking and an increased locomotor activity, respectively (Brito et al., 2013; Diop et al., 2015). It is therefore possible that we have missed a potential pleiotropic effect of the L1024V mutation on the behavior of T. urticae .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, reversion to susceptibility has often been observed in laboratory or field populations of insects, and fitness costs or deleterious effects of resistance genes have been observed (mosquito Culex pipiens: Berticat et al, 2002;Berticat et al, 2004;Bourguet et al, 2004 : Foster et al, 2003;Foster et al, 2005). If resistance factors have disadvantageous effects on fitness, it is expected that the frequencies of resistance factors within insect populations tend to decrease under no insecticide environments, which results in the tendency towards a decrease in levels of resistance to insecticides within insect populations (Crow, 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Some strains of M. persicae with over expressing high levels of carboxylesterase (due to structural gene amplification) show a reduced tendency to move away from senescing leaves compared with susceptible counterpart (Foster et al 1997(Foster et al , 2003. This behaviour caused higher mortality during worst winter weather conditions and so can be regarded as a deleterious pleiotropic effect of pesticide resistance.…”
Section: Maladaptive Behaviormentioning
confidence: 99%
“…This behaviour caused higher mortality during worst winter weather conditions and so can be regarded as a deleterious pleiotropic effect of pesticide resistance. Studies have been shown that peachpotato aphids caring both gene amplification and the knock down mutation has reduced response to alarm pheromone (Foster et al, 2003).…”
Section: Maladaptive Behaviormentioning
confidence: 99%
See 1 more Smart Citation